The Pro-Gly or Hyp-Gly Containing Peptides from Absorbates of Fish Skin Collagen Hydrolysates Inhibit Platelet Aggregation and Target P2Y12 Receptor by Molecular Docking - Qi Tian; Shi-Ming Li; Bo Li (Foods, 2021)
Previous studies found that the collagen hydrolysates of fish skin have antiplatelet activity, but this component remained unknown. In this study, eleven peptides were isolated and identified in the absorbates of Alcalase-hydrolysates and Protamex®-hydrolysates of skin collagen of H. Molitrix by reverse-phase C18 column and HPLC-MS/MS. Nine of them contained a Pro-Gly (PG) or Hyp-Gly (OG) sequence and significantly inhibited ADP-induced platelet aggregation in vitro, which suggested that the PG(OG) sequence is the core sequence of collagen peptides with antiplatelet activity. Among them, OGSA has the strongest inhibiting activities against ADP-induced platelet aggregation in vitro (IC50 = 0.63 mM), and OGSA inhibited the thrombus formation in rats at a dose of 200 μM/kg.bw with no risk of bleeding. The molecular docking results implied that the OG-containing peptides might target the P2Y12 receptor and form hydrogen bonds with the key sites Cys97, Ser101, and Lys179. As the sequence PG(OG) is abundant in the collagen amino acid sequence of H. Molitrix, the collagen hydrolysates of H. Molitrix might have great potential for being developed as dietary supplements to prevent cardiovascular diseases in the future.